Pengaruh Produk Domestik Regional Bruto Terhadap Jumlah Timbulan Sampah di Provinsi Aceh - Sukirman, Auni Alifah; Junaedi, Putri Adhriani; Sihaloho, Estro Dariatno (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2024)
One of the indicators of a healthy environment is proper waste management. However, waste has become a global issue, with approximately 40% of the world’s waste being improperly managed, and its volume is projected to reach 3.40 billion metric tons by 2050. In Indonesia, 65.83% of waste is still disposed of in landfills, with a total volume of 68.7 million tons per year, the majority of which consists of organic waste (41.27%) and household waste (38.28%). This study aims to analyze the impact of Gross Regional Domestic Product (GRDP) and other factors such as population size and education level on the amount of waste volume in Aceh Province from 2018 to 2020. Using a quantitative approach, secondary data obtained from the Central Bureau of Statistics (BPS) of Aceh Province were used in a panel data regression model. The results of the study show that GRDP and population size have a significant and positive influence on waste volume. These findings confirm that economic growth and population density increase the amount of waste, while higher education can reduce waste generation. Based on these results, it is expected that the government can formulate effective waste management policies, including improving the education level of the community to reduce the amount of waste produced. This study provides important insights for the government in planning better waste management in Aceh Province.